Soils, land, and food : managing the land during the twenty-first century - Wild, Alan (Cambridge University Press, 2003)
A major challenge of the twenty-first century will be to ensure sufficient global food production to cope with the ever-increasing world population. Soils, Land and Food is aimed at undergraduates, graduates, agricultural scientists and policy makers and describes how technological approaches to soil management can increase and sustain food production.